2021
DOI: 10.3390/w13081113
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Optimization of eDNA/eRNA Sampling Technologies for Marine Biosecurity Surveillance

Abstract: The field of eDNA is growing exponentially in response to the need for detecting rare and invasive species for management and conservation decisions. Developing technologies and standard protocols within the biosecurity sector must address myriad challenges associated with marine environments, including salinity, temperature, advective and deposition processes, hydrochemistry and pH, and contaminating agents. These approaches must also provide a robust framework that meets the need for biosecurity management d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 200 publications
1
75
0
Order By: Relevance
“…The 18S rRNA data also showed sensitivity to multiple freeze–thaw cycles of the samples. The available (mostly anecdotal) evidence of the effect of multiple defrosting on DNA integrity suggests that even one freeze–thaw cycle can reduce eDNA signal (Bowers et al, 2021). However, it is rarely the case that metabarcoding library construction is achieved without repetition of the PCR step (and thus multiple freeze–thawing of DNA material) for at least some samples (e.g., troubleshooting and adjusting amplification conditions for problematic samples).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 18S rRNA data also showed sensitivity to multiple freeze–thaw cycles of the samples. The available (mostly anecdotal) evidence of the effect of multiple defrosting on DNA integrity suggests that even one freeze–thaw cycle can reduce eDNA signal (Bowers et al, 2021). However, it is rarely the case that metabarcoding library construction is achieved without repetition of the PCR step (and thus multiple freeze–thawing of DNA material) for at least some samples (e.g., troubleshooting and adjusting amplification conditions for problematic samples).…”
Section: Discussionmentioning
confidence: 99%
“…However, metabarcoding is inherently complex, with many technical and analytical steps that inevitably vary among users, as well as multiple reputable but distinct metabarcoding workflows (Cristescu, 2014; Goldberg et al, 2016; Murray et al, 2015; Zaiko et al, 2018). Virtually all steps in the workflow vary among laboratories and individual studies, including sampling, preservation methods, DNA extraction, PCR amplification protocols, library preparation methods, sequencing platforms and bioinformatic pipelines (Bailet et al, 2020; Bowers et al, 2021). This creates a significant challenge for the standardization of protocols and the implementation of a unified, cross‐calibrated approach.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been previously shown that larger pore filters can be as effective as finer pore filters for species detection from waterborne eDNA (Sepulveda et al, 2019; Wittwer et al, 2018), more data are needed on the selectivity of different membrane pore sizes towards specific NA types and fractions (Bowers et al, 2021). Rarely (if at all) do such comparative studies involve technical efficiency assessment to address time/cost inputs in the context of molecular signal recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Invasions of NIS are heavily facilitated in marine environments by the global shipping industry, and are becoming an increasingly pervasive global issue (reviewed by Bowers et al, 2021;Duarte et al, 2020). Timely detection, and management responses are of paramount importance (Lehtiniemi et al, 2015), and traditional surveillance may overlook NIS when the population is still localized and in low densities (Freire et al, 2014).…”
Section: Edna For Large-scale Monitoring Of Nonindigenous and Invasiv...mentioning
confidence: 99%